Relaxing the assumption of unrelatedness in the numerator and denominator of likelihood ratios for DNA mixtures. (March 2021) - Allen, Paul Stafford; Pugh, Simone N.; Bright, Jo-Anne; Taylor, Duncan A.; Curran, James M.; Kerr, Zane; Buckleton, John S.
Highlights: Donors under the prosecution and alternate propositions are usually assumed unrelated. The effect of relaxing this assumption is examined by simulation. We study a limited set of examples. Ignoring relatedness leads to the LR being understated approximately 95 % of the time. Abstract: DNA mixtures will have multiple donors under both the prosecution and alternate propositions when assigning a likelihood ratio for forensic DNA evidence. These donors are usually assumed to be unrelated to each other. In this paper, we make a small, preliminary examination of the potential effect of relaxing this assumption. We consider the simple situation of a two-person mixture with no dropout and a two-person major/minor mixture with dropout of the minor contributor. We make no adjustment for subpopulation effects. Mixtures were simulated under two assumptions: 1. that the donors were siblings 2. or that they were unrelated. Both unresolvable and major/minor mixtures were considered. We compared the likelihood ratio assuming sibship with the likelihood ratio assuming no relatedness. The LR for hypotheses assuming no relatedness is less than the LR assuming relatedness approximately 95% of the time when relatives are present in the mixture.